1993
DOI: 10.1200/jco.1993.11.4.661
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase II trial of high-dose interleukin-2 either alone or in combination with interferon alfa-2b in advanced renal cell carcinoma.

Abstract: We conclude that both IL-2 and IL-2/IFN therapy have activity in metastatic renal cell carcinoma. In particular, therapy with high-dose IL-2 alone produces meaningful and durable responses with manageable and reversible toxicity. This study supports the contention that high-dose IL-2 represents the treatment of choice in selected patients with advanced renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
67
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(70 citation statements)
references
References 37 publications
2
67
0
1
Order By: Relevance
“…However, when patients with metastatic renal cell carcinoma were treated with the same combination of cytokines, the objective response rate obtained was 11-38% (Rosenberg et al, 1989b;Atkins et al, 1991); thus the addition of INF-a to the treatment of renal cell carcinoma with IL-2 did not appear to increase the response. It was argued that response rate might be related to the dose of cytokines given (Rosenberg et al, 1989b), although increasing cytokine doses resulted in higher toxicity (Rosenberg et al, 1989b;Atkins et al, 1991).…”
mentioning
confidence: 93%
“…However, when patients with metastatic renal cell carcinoma were treated with the same combination of cytokines, the objective response rate obtained was 11-38% (Rosenberg et al, 1989b;Atkins et al, 1991); thus the addition of INF-a to the treatment of renal cell carcinoma with IL-2 did not appear to increase the response. It was argued that response rate might be related to the dose of cytokines given (Rosenberg et al, 1989b), although increasing cytokine doses resulted in higher toxicity (Rosenberg et al, 1989b;Atkins et al, 1991).…”
mentioning
confidence: 93%
“…Atkins and others, 39 in their randomized phase 2 trial of high-dose IL-2 with and without interferon-α, found no difference in response in either group. However, toxicity was higher with the addition of interferon-α.…”
Section: Interferon and Il-2 Combination Regimensmentioning
confidence: 94%
“…Results of a review 39 of more than 1400 patients receiving interferon-α and IL-2 indicated an overall RR of 20% for the combination, and found that 3%-5% of patients had CRs.…”
Section: Interferon and Il-2 Combination Regimensmentioning
confidence: 99%
“…A sxnergistic response was confirmed in mice (Cameron et al 1988) and this led to the development of combination regimens that were associated wvith an ox erall response rate of up to 29%7 (Atzpodien et al 1990. 1991: Palmer et al 1993: Canobbio et al 1996b: Gause et al 1996 Savage et al 1996) wxith a median survival of 8-12 months (Facendola et al 1995: Canobbio et al 1996a Correspondence to: GC Jayson hN-potension and creatinine elexvation (Atkins et al 1993: Gause et al. 1996. factors that led to the premature discontinuation of therapy in 14% of patients (Facendola et al 1995).…”
mentioning
confidence: 99%
“…hN-potension and creatinine elexvation (Atkins et al 1993: Gause et al 1996. factors that led to the premature discontinuation of therapy in 14% of patients (Facendola et al 1995).…”
mentioning
confidence: 99%